Edificar em Minas Gerais no século XVIII: a cultura das oficinas de construções religiosas luso - brasileiras - Patrícia Daniele Urias Pinto (2013)
The present dissertation deals with the Luso-brazilian construction sites, places where the construction field professionals were trained and places where occurred exchanges of experiences, skills and knowledges related to the seventeenth-century universe. The research focus is on the historical process that began in Portugal, in the construction sites of São Vicente de Fora, Santa Engrácia and Mafra National Palace, learning fields where Filippo Terzi (15201597), João Antunes (16421712) and João Frederico Ludovice (16731752), acted, respectively. Professionals who had a bold mentality for the period and who undertook the possible changes in the Portuguese architectural universe, considered lagged with regard to the modifications carried out in countries like Italy and France. The historical approach achieves the American Portuguese territory, more precisely the Captaincy of Minas Gerais, where we analize the performances of professionals involved in its constructions. The constructions analized learning fields were the churches of Nossa Senhora do Bom Sucesso (Caeté), São Francisco de Assis and Nossa Senhora do Carmo (Ouro Preto). Antônio da Silva Herdeiro, Domingos Moreira de Oliveira and João Álvares Vianna, respectively, were professionals at the forefront of these works. The necessary procedures for the auction of these works were analized, as well as the constructive process of these churches. The approach culminates with the analysis of the workshop of São Francisco de Assis, pointing its construction steps.